STABLE ISOTOPE RECORD OF THE TERMINAL NEOPROTEROZOIC KROL PLATFORM IN THE LESSER HIMALAYAS OF NORTHERN INDIA - Kaufman A.J.; Jiang G.; Christie-Blick N.; Banerjee D.M.; Rai V. (My University, 2006)
The terminal Neoproterozoic succession in the Lesser Himalaya of India, including the Infra Krol Formation and Krol Group, represent the thickest known accumulation of carbonate strata of this time period, and hence is an ideal target for chemostratigraphic and sequence stratigraphic investigation. High-resolution analyses reveal several negative δ13C excursions. Only one of these is related to known Neoproterozoic ice ages, and many vary in amplitude and stratigraphic position in an oblique regional transect of the platform. A combination of stratigraphic and geochemical tests, and comparison with sections elsewhere, leads to an evaluation of the relative contributions of primary and secondary signals. Two excursions are associated with abrupt facies changes associated with shallowing and accumulation of carbonate in organic-rich restricted environments, or with karstification of a subaerially exposed platform; these are currently interpreted to be diagenetic artifacts. Other negative δ13C excursions are recorded in open marine transgressive facies, and are interpreted to represent biogeochemical anomalies of global significance. The magnitude of these excursions, however, is complicated by their lateral inconsistency between adjacent sections. Two interpretations are proposed. One possibility is that the observed isotopic inconsistency is due to diagenesis not revealed by the application of existing geochemical criteria. A composite δ13C curve constructed under this assumption is broadly consistent with that documented elsewhere, and may reflect modest biogeochemical changes of global scale. An alternative interpretation is that the inconsistency of δ13C values relates to stratigraphic hiatus between correlated horizons, incomplete sampling, and/or lack of appropriate carbonates facies. The composite δ13C curve constructed under this assumption shows large-magnitude (up to 15‰) negative δ13C anomalies that are taken to imply remarkable perturbations of ocean geochemistry and the episodic input of13C-depleted alkalinity during terminal Neoproterozoic time. © 2006 Elsevier B.V. All rights reserved.
Keywords: ISOTOPE; KROL GROUP; NEOPROTEROZOIC; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская